Associations of Body Mass Index With Laboratory and Biomarkers in Patients With Acute Heart Failure. (January 2017) - Streng, Koen W.; ter Maaten, Jozine M.; Cleland, John G.; O'Connor, Christopher M.; Davison, Beth A.; Metra, Marco; Givertz, Michael M.; Teerlink, John R.; Ponikowski, Piotr; Bloomfield, Daniel M.; Dittrich, Howard C.; Hillege, Hans L.; et al.
Abstract : Background—: Plasma concentrations of natriuretic peptides decline with obesity in patients with heart failure. Whether this is true for other biomarkers is unknown. We investigated a wide range of biomarker profiles in acute heart failure across the body mass index (BMI) spectrum. Methods and Results—: A total of 48 biomarkers, assessing multiple pathophysiological pathways, were measured in 2033 patients included in PROTECT (Placebo-Controlled Randomized Study of the Selective A1 Adenosine Receptor Antagonist Rolofylline for Patients Hospitalized With Acute Decompensated Heart Failure and Volume Overload to Assess Treatment Effect on Congestion and Renal Function), a trial comparing the effects of rolofylline to placebo in patients with acute heart failure. Patients were classified into 4 groups according to BMI (<25, 25–30, 30–35, and >35 kg/m 2 ). Of 2003 patients with known weight and height, mean age was 70±12 years and 67% were men. Patients with a higher BMI (>35 kg/m 2 ) had higher blood pressures, were younger, and were more often women. Median levels of brain natriuretic peptide were 550 pg/mL in patients with a BMI <25 kg/m 2 and 319 pg/mL in patients with a BMI >35 kg/m 2 ( P <0.001). Multivariable regression revealed that brain natriuretic peptide (β=−0.250; P <0.001) and receptor for advanced glycation endproducts (β=−0.095; P <0.007) were inversely correlated to BMI, whereas higher levels of uric acid (β=0.164; P <0.001), proadrenomedullin (β=0.171; P <0.001), creatinine (β=0.118; P =0.003), sodium (β=0.101; P =0.006), and bicarbonate (β=0.094; P =0.009) were associated with higher BMI. No significant interaction was seen between these 7 biomarkers and BMI on 180-day mortality. Conclusions—: The plasma concentrations of several biomarkers are either positively or negatively influenced by BMI. These findings suggest that these markers should be interpreted with caution in patients with obesity. Although concentrations differ, their prognostic value for mortality up to 180 days did not differ. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00354458. Abstract : Supplemental Digital Content is available in the text.